Synthesis and characterization of isoindigo‐based polymers using CH‐arylation polycondensation reactions for organic photovoltaics. Issue 20 (6th August 2014) - Elsawy, Walaa; Kang, Hongkyu; Yu, Kilho; Elbarbary, Ahmed; Lee, Kwanghee; Lee, Jae‐Suk
ABSTRACT A series of three new low bandgap donor–acceptor–donor–acceptor/ (D–A–D–A/) polymers have been successfully synthesized based on the combination of isoindigo as the electron‐deficient acceptor and 3, 4‐ethylenedioxythiophene as the electron‐rich donor, followed by CH‐arylation with different acceptors (4, 7‐dibromo[c][1, 2, 5]‐(oxa, thia, and/or selena)diazole (4a‐c)). These polymers were used as donor materials for photovoltaic applications. All of the polymers are highly stable and show good solubility in chlorinated solvents. The highest power conversion efficiency of 1.6% was achieved in the bulk heterojunction photovoltaic device that consisted of poly ((E)−6‐(7‐(benzo‐[c][1, 2, 5]‐thiadiazol‐4‐yl)−2, 3‐dihydrothieno‐[3, 4‐b][1, 4]dioxin‐5‐yl)−6′‐(2, 3‐dihydrothieno‐[3, 4‐b][1, 4]‐dioxin‐5‐yl)−1, 1′‐bis‐(2‐octyldodecyl)‐[3, 3′‐biindolinylidene]‐2, 2′‐dione) as the donor and PC61BM as the acceptor, with a short‐circuit current density (Jsc) of 8.10 mA/cm2, an open circuit voltage (Voc) of 0.56 V and a fill factor of 35%, which indicates that these polymers are promising donors for polymer solar cell applications. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2926–2933